Boxed In: Transcultural Practice in the Works of Nineteenth-Century Haudenosaunee Artists - Lowell, Rebecca. (2018)
Abstract: This thesis explores works by Haudenosaunee artists from the first half of the nineteenth century, suggesting that the study of material culture allows for alternative ways of investigating the individualized experiences of Native people. More specifically, I look at watercolors by the Tuscarora artist Dennis Cusick and silverwork from the decades before and after Cusick was alive. These objects serve as evidence of the complex histories that remain understudied, yet deserve further time and attention in service of challenging staid national narratives of Native American Indian and Euro-American encounters. In illustrating the limitations of superficial visual judgments or impressions, and identifying the power structures and histories that contribute to the specific choice of forms and materials used by Haudenosaunee artists and artisans, I demonstrate the potential of transcultural praxis as a way to bring to light suppressed or overlooked histories.; Thesis (M.A.)--Tufts University, 2018.; Submitted to the Dept. of Art and Art History.; Advisor: Eva Hoffman.; Committee: Eric Rosenberg, and William Moore.; Keywords: Art history, Native American studies, and American studies.